Entre a hegemonia e a polissemia: a Política de Educação e Desenvolvimento para o SUS no contexto do Brasil contemporâneo - Pinheiro, Verônica de Souza (2007)
The proposal of the Unified Health System Policy (SUS) has been considered one of the most democratic public policies in Brazil. In spite of this, its implementation in a context of social inequalities has demanded significant efforts. From a socio-constructionist perspective on social psychology, the study focused on the National Policy for Permanent Education in Health for the Unified Health System (SUS), launched by the Brazilian government in 2004, as an additional effort to improve practices and accomplish the effective implementation of the principles and guidelines of the Policy. Considering the process of permanent interdependencies between these propositions and the socio-political and cultural context, the study aimed to identify the discursive constructions articulated in the National Policy for Permanent Education in Health for the Unified Health System (SUS) and how they fit into the existing power relations of ongoing Brazilian socio-political context. Subject positionings and action orientation offered to different social actors by these discursive constructions and the kind of practices allowed were also explored, as well as the implementation of the proposal in Rio Grande do Norte state and how this process was perceived by the people involved. The information produced by documental analyses, participant observation and interviews was analyzed as proposed by Institutional Ethnography. It evidenced the inter-relations between the practices of different social actors, the conditions available for those practices and the interests and power relations involved. Discontinuities on public policies in Brazil and the tendency to prioritize institutional and personal interests, in detriment of collective processes of social transformation, were some of obstacles highlighted by participants. The hegemony of the medical model and the individualistic and curative intervention practices that the model elicits were also emphasized as one of the drawbacks of the ongoing system. Facing these challenges, reflexivity and dialogism appear as strategies for a transformative action, making possible the denaturalization of ongoing practices, as well as the values and tenets supporting them